2021
DOI: 10.1111/jgh.15515
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized tandem gastroscopy pilot study of linked color imaging versus white light imaging for detection of upper gastrointestinal lesions

Abstract: Background and Aim Gastrointestinal (GI) lesions may have subtle morphological changes. Linked color imaging (LCI) combines narrow‐band wavelength light and white light imaging (WLI) in appropriate balance to enhance lesion detection. We compared the detection rates of upper GI lesions using LCI and WLI. Method Patients were randomized in a 1:1 ratio to receive tandem gastroscopy with WLI inspection followed by LCI, or vice versa. Endoscopic examination was performed using the EG‐L590ZW gastroscope and the LAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…IEE improves the detection of precancerous atrophic and metaplastic gastric mucosa and shows promise as a tool for mapping the severity of metaplastic change. 63 , 64 , 65 , 66 , 67 IEE also enables endoscopic diagnosis of H. pylori infection status. 68 , 69 IEE, especially with magnification, aids in the characterization of gastric neoplasia but detection has been more challenging (Figure 5 ), A multi‐centered randomized controlled trial of over 4500 patients comparing second‐generation NBI with white light imaging showed no significant difference in the detection of early GC.…”
Section: Image‐enhanced Endoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…IEE improves the detection of precancerous atrophic and metaplastic gastric mucosa and shows promise as a tool for mapping the severity of metaplastic change. 63 , 64 , 65 , 66 , 67 IEE also enables endoscopic diagnosis of H. pylori infection status. 68 , 69 IEE, especially with magnification, aids in the characterization of gastric neoplasia but detection has been more challenging (Figure 5 ), A multi‐centered randomized controlled trial of over 4500 patients comparing second‐generation NBI with white light imaging showed no significant difference in the detection of early GC.…”
Section: Image‐enhanced Endoscopymentioning
confidence: 99%
“…The advent of image‐enhanced endoscopy (IEE) has addressed some of the shortcomings of white light examination in detecting mucosa at risk of GC and the detection and characterization of gastric neoplasia. IEE improves the detection of precancerous atrophic and metaplastic gastric mucosa and shows promise as a tool for mapping the severity of metaplastic change 63–67 . IEE also enables endoscopic diagnosis of H. pylori infection status 68,69 .…”
Section: Image‐enhanced Endoscopymentioning
confidence: 99%
“…There are several reports on the usefulness of image-enhanced endoscopy (i.e., linked color imaging, narrow-band imaging, and i-scan optical enhancement) for gastric cancer detection before eradication [35-38]. However, there are limited reports regarding detection of gastric cancer after eradication by image-enhanced endoscopy.…”
Section: Comparison Of Risk Factors For Primary and Metachronous Gastric Cancer After H Pylori Eradicationmentioning
confidence: 99%
“…Diagnosis of GIM needs close attention from an endoscopist for subtle mucosal changes, which can be easily overlooked 8 . Because white light endoscopy (WLE) alone is not sufficient to diagnose these changes, various techniques have been developed to enhance the sensitivity of detection, such as image-enhanced endoscopy (IEE) with or without magnification 9 10 11 , otherwise an additional random biopsy (Sydney protocol) to cover the potential missing lesions is recommended for implementation 12 . In 2019, British Society of Gastroenterology guidelines recommended the use of IEE, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there has been no direct comparison of the performance status of targeted biopsy with NBI and NBI-targeted biopsy plus random biopsies under the Sydney protocol in patients with GIM. Moreover, all previous studies related to the benefit of targeted biopsy involved experts in NBI 9 10 11 . Therefore, this study aimed to compare the performance status of these two strategies for diagnosis of extensive GIM, performed gastroenterologists who were not expert at NBI.…”
Section: Introductionmentioning
confidence: 99%